2019
DOI: 10.21071/az.v68i261.3947
|View full text |Cite
|
Sign up to set email alerts
|

Suplementação de lisina digestível influencia o ganho de peso de frangos de corte aos 21 dias de idade

Abstract: Este estudo analisou os efeitos da lisina digestível sobre os parâmetros de desempenho, morfometria e qualidade do músculo do peito (Pectoralis major) de frangos de corte com 21 e 42 dias de idade. Foram realizados dois experimentos em um delineamento inteiramente casualizado, com cinco tratamentos e oito repetições de 30 aves por parcela. As dietas foram formuladas de acordo com as exigências nutricionais para cada fase de desenvolvimento das aves, com diferentes níveis de lisina digestível durante a fase ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%
“…Contrary to the observations of the present study, Ghazanfari et al (2010) observed that in broilers that incremental changes in dietary protein levels did increase feed intake and improved weight gain and feed conversion, compared with a low level of protein in the diet. Jafarnejad et al Improved productive performance of broiler chickens has been observed when increased over NRC recommendation the levels of lysine (Oliveira et al, 2013;Bernal et al, 2014;Quadros et al, 2019;Zarghi et al, 2020) and methionine plus cystine (Goulart et al, 2011). In the current study, the increase in crude protein increased the lysine concentration in the diets over the NRC recommendations; however, the crude protein increase in diets did not have evident increase on the levels methionine plus cystine in the used diets over the NRC recommendations.…”
Section: Growth Performancecontrasting
confidence: 47%